PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP BRAND IMAGE (Penelitian Terhadap Busana Muslim Merek Zoya di DKI Jakarta) - Nurianti, Amanda; Suhartati, Suhartati (Ibs Press, 2024)
This study aims to examine and analyze the effect of Integrated Marketing Communication (advertising, sales promotion, personal selling, public relations, direct marketing and internet marketing on the Brand Image